Respon Pertumbuhan dan Produksi Bengkuang (Pachyrhizus erosus L.) Terhadap Perendaman Auksin dan Pengaturan Jarak Tanam - Tambunan, Fadia S; Kurniawan, Dedi; Nadhira, Ahmad (JURNAL AGROPLASMA, 2025)
This study aimed to evaluate the effect of auxin soaking and planting spacing on the growth and yield of yam bean (Pachyrhizus erosus L.). The experiment was conducted in Paya Pasir, Medan Marelan, North Sumatra, from March to July 2025, using a factorial Randomized Block Design (RBD) with two factors: auxin soaking duration (0 hours, 1 hour, 2 hours) and planting spacing (20×20 cm, 20×25 cm, 20×30 cm), each with three replications. The results showed that auxin soaking had a significant effect on vine length at 3 weeks after planting (WAP), whereas planting spacing had no significant effect on all measured parameters. The interaction between the two factors significantly affected vine length, tuber weight per sample, tuber weight per plot, and brix value. The best combination was obtained from treatment P1J1 (1 hour soaking and 20×25 cm spacing), producing the highest tuber weight per plot (574 g). These findings indicate that a combination of moderate auxin dosage and close planting spacing can enhance the productivity of yam bean. Keywords: jicama, auxin, planting spacing, growth, yield